IDEOLOGICAL SHIFT OF TEXT AND THE INFLUENCE OF TRANSLATION IDEOLOGY IN THE NOVEL “HALF OF YELLOW SUN” - Husnawati . .; Amrin . Saragih; Zainuddin . . (LINGUISTIK TERAPAN, 2021)
ABSTRACTThis research paper concerned with the analysis of factor affecting ideological shift of text in the translation of literary work. As the data source, a novel entitled 'half of yellow sun' a work of Chimamanda Adichie was analyzed. The analysis was specified to clauses taken from the English and Indonesian version of the novel, as the data. Further, the researcher applied descriptive qualitative approach in collecting and analyzing the data. Halliday’s theory of metafunction, specified on the analysis of transitivity system was used as main theory. Moreover, the theory of ideology in translation was adopted in the analysis, as causal factor to see how translation ideology cause the ideological shift of text in translation. Then, the result of the analysis revealed that the intermetafunctional shift is the most significant category found in the text (90.24%), while the intra-metafunctional shift was only found once (9.75%).   It proved that there were significant change of ideology of text showed by the changing of the process of transitivity system. Morever, the result of analysis releaved that, the ideological shifts of text were mostly affected by domestication ideology with percentages 78.05%, and foreignization ideology by percentages 21.95% or equal to a quarter of the whole clauses. It means that the translator produced the translation based on her goal and point of view and ideology of target language's culture and trying to make the text as closely as possible to the target readers’ language. It means the ideological shift of text were affected by translation ideology in which the translator produced the translation based on her goal and point of view and ideology of target language's culture and trying to make the text as closely as possible to the target readers’ language.Keywords: Systemic Functonal Linguistics, Translation, Discourse Analysis, Ideological Shift, literary work